2018
DOI: 10.1590/abd1806-4841.20187317
|View full text |Cite
|
Sign up to set email alerts
|

Papular elastorrhexis: a rare and benign disease

Abstract: Papular elastorrhexis is an acquired disease of elastic tissue; considered rare, its etiology and pathogenesis remain unknown. The vast majority of cases occur in women in the first or second decade of life. The disease manifests as multiple uniformly-sized, circumscribed, hypochromic and achromic papules located predominantly on the trunk and upper extremities. The lesions are generally asymptomatic and have a stable evolution over years. Its diagnosis is based on clinical and histopathological findings. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…[ 3 ] Other differential diagnoses include papular acne scars, anetoderma, mid-dermal elastolysis, and postinflammatory elastolysis. [ 4 ]…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 3 ] Other differential diagnoses include papular acne scars, anetoderma, mid-dermal elastolysis, and postinflammatory elastolysis. [ 4 ]…”
mentioning
confidence: 99%
“…Differential diagnoses of PE may also include dermatofibroma, with the most prevalent dermoscopic pattern being a delicate peripheral pigmented network and a central white network [3] . Other differential diagnoses include papular acne scars, anetoderma, mid-dermal elastolysis, and postinflammatory elastolysis [4] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 The reduction of elastic fibers around perifollicular or sebaceous units was similar to papular elastorrhexis. 4,[16][17][18][19] Amadeu and colleagues 20 reported changes in the elastic fibers in both hypertrophic and keloid scars, with thinning and disturbed elastic fibers and 40% increased elastin content in keloid scars in the deep dermis compared with those in normal skin. The content and quality of elastic fibers reportedly change during abnormal scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical clinical manifestations are often multiple, asymptomatic, firm, circumscribed, oval to round papules with a diameter of about 1-5 millimeters; the etiology and pathogenesis of PE remain unknown; also, it has a stable evolution over the year; reliable treatment option was absent to date; the diagnosis is mainly based on classic clinical manifestations and typical histopathological evidence of reduction even the absence of elastic fibers. 1,2 The dermoscopy examination was considered a potential tool for the non-invasive diagnosis of PE, with unique findings with honeycomb-like reticular pigment surrounded by radial pigment without vessel involvement, was proposed. 3 Interestingly, different from the previous report, we found that the vessel structure was involved in our case presented; the findings also support that the vessel involvement may also be the potential dermoscopic clues; the central yellow-white unstructured area was consistent of the reduction and the absence of elastic fibers in histologically, also the vessel involvement may represent the infiltration of inflammatory cells and the perivascular proliferation in super dermis.…”
Section: Lettermentioning
confidence: 99%